FAKTOR YANG MEMPENGARUHI MINAT BERLANGGANAN PADA PELANGGAN ASTINET (KOMPARASI ANTARA SEGMEN BISNIS DAN SEGMEN GOVERMENT UNIT BGES PADA PT TELKOM PADANG ) - RAMADHANIEL, FAJRY; AZMAN, HERU AULIA (STIE Perbankan Indonesia, 2018)
This research aims to find out the influence of the price of the product features and after-sales service on intention to subscribe on the subscriber Astinet business segment and government PT Telkom field. From the result of a survey conducted by researchers the number of customers and business segment Astinet goverment as much as 408 customers, after an overview of the library and the formulation of the hypothesis, obtained data from the spread of the questioner to 202 customers who obtained with Forcible Entry sampling. This shows that the price variables affect significant positive impact on the interest subscribe on both segments. So also on the features variable has the value of the significance of 0.001 smaller than α 0.05 or the value of t_count>t table_namely 3,389>1.66 with β 0,417value with positive direction on business segment, the segments of the government can be known that the product features variable has the value of the significance of the lowest infection rate was from 0.00 greater than α 0.05 or the value of t_count>t table_namely 3,849> 1.66 with β 0,412 value with positive direction. This shows that the product features variable significant effect against the decision to subscribe to on the second segment. While in the variable after sales service on the business segment can be known that the after sales service variable has the value of the significance of 0,023 greater than α 0.05 or the value of t_count>t table_namely 2,312> 1.66 with β 0,214 value with positive direction, the segments of the government can be known that the after sales service variable has the value of the significance of 0,194 greater than α 0.05 or the value of t_count>t table_namely 1,986 > 1.66 with value β 0.179 % in the direction of positive.